2010
DOI: 10.1037/a0017052
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity amidst challenge: Reflections of a Latina supervisor.

Abstract: This paper discusses the experiences of a Latina supervisor who practices from a multiculturally competent framework, including cultural issues, ethical issues, and organizational issues. Examples are provided throughout the paper to illustrate the flexibility and sensitivity required when attempting to navigate the interaction of multicultural identities in supervision. Reflections are then offered as they relate to the experiences of the Latina supervisor, including the salience of sociocultural background, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Seventy‐five percent of the data set (18 of 24 articles) revealed that culturally competent supervisors needed to adopt many dynamic and purposeful positions, offering their supervisees clear instructions for discussing, analyzing, and applying multicultural principles and techniques in clinical practice. Several articles suggested supervisors who demonstrated openness to self‐reflection and exploration of personal biases and assumptions, honored and attended to all socio‐political‐cultural domains, and offered comfort and encouragement when needed greatly benefited the supervisees (Ancis & Marshall, ; Butler‐Byrd, ; Reynaga‐Abiko, ; Singh & Yuk Sim Chun, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy‐five percent of the data set (18 of 24 articles) revealed that culturally competent supervisors needed to adopt many dynamic and purposeful positions, offering their supervisees clear instructions for discussing, analyzing, and applying multicultural principles and techniques in clinical practice. Several articles suggested supervisors who demonstrated openness to self‐reflection and exploration of personal biases and assumptions, honored and attended to all socio‐political‐cultural domains, and offered comfort and encouragement when needed greatly benefited the supervisees (Ancis & Marshall, ; Butler‐Byrd, ; Reynaga‐Abiko, ; Singh & Yuk Sim Chun, ).…”
Section: Resultsmentioning
confidence: 99%
“…Ladany () described the multicultural supervisory alliance as a foundation based on mutual trust and satisfaction upon which culturally competent experiences are developed. Analysis of the findings from 80% of the data set (19 of 24 articles) demonstrated when the supervisory alliance was grounded in a respectful and collaborative relationship, supervision was viewed as safe and optimal learning occurred (Dressel et al., ; Gardner, ; Reynaga‐Abiko, ).…”
Section: Resultsmentioning
confidence: 99%
“…This perspective was reiterated in the current American Psychological Association Guidelines for Clinical Supervision in Health Service Psychology that promote the empowerment and resilience of culturally diverse populations through focused attention in supervision to the identities and sociocultural contexts of clients as well as supervisees (American Psychological Association, 2014). In response, several theories of supervision and counseling, situated in critical, postcolonial, multicultural, and feminist ideologies were developed that focused on culture, empowerment, and liberation in an effort to address issues of power and oppression in psychotherapeutic work (Butler-Byrd, 2010; Falicov, 2014; Hernández et al, 2010; MacKinnon, Bhatia, Sunderani, Affleck, & Smith, 2011; Reynaga-Abiko, 2010; Singh & Chun, 2010).…”
mentioning
confidence: 99%
“…A postcolonial perspective, therefore, exceeds the multicultural stance because it challenges current normativity by contesting the cultural embeddedness of individualistic norms and de-contextualized theories on which supervision and therapy are built (Hernández et al, 2010). A critical postcolonial- and resilience-based approach seeks to develop new frameworks that acknowledge a diversity of experience and integrate multiple ways of knowing and attention to cultural diversity (Butler-Byrd, 2010; Hernández et al, 2010; Reynaga-Abiko, 2010; Singh et al, 2010). By focusing on the role of social context and the power structure in developing and maintaining emotional distress, clients and supervisees are seen as multifaceted, intersectional, and embedded in their context rather than within compartmentalized identities (Hernández et al, 2010; Porter & Vasquez, 1997; Singh et al, 2010).…”
mentioning
confidence: 99%
“…By acting out their own internalized racism or focusing solely on racial and ethnic identity without recognizing multiple layers of their supervisees' identities, these supervisors may unwittingly commit microaggressions against trainees of color (Butler-Boyd, 2010; Jernigan et al, 2010; Murphy-Shigematsu, 2010). Because trainees of color often assume supervisors of color are culturally competent (Reynaga-Abiko, 2010), they may be more disappointed when their supervisors of color act based on their own stereotypes, internalized oppression, and unchecked biases than if a White supervisor behaved similarly.…”
mentioning
confidence: 99%